Letters of affiliation to the Institute of the Brothers of the Christian schools - Alburo, Josefina H. (Animo Repository, 1988)
On the feast of St. John Baptist de La Salle celebrated on 7 April 1988, Josefina Alburo and Gines Rivera were awarded the Letters of Affiliation to the Institute of the Brothers of the Christian Schools. Alburo served as principal of DLS and continues to serve as Special Assistant to the President. Architect Rivera is architect-in-residence of the University.